Teaching medical law in contemporary healthcare setting: challenges and opportunities - Jahn Kassim, Puteri Nemie (2019)
As the medical profession deals with a person’s two most precious commodities, namely, life and health, any mistake that results in death or disability will usually trigger claims in the court of law. This is due to the fact that victims of medical injuries usually find such mistakes hard to grasp as medicine is to cure and not otherwise. Thus, in their perception, such mistakes could have been avoided if the medical practitioner had taken proper care. Therefore, it can be seen that, the constant intervention of law into medical practice has created not only more rights for the patients but more liabilities for the medical practitioners. Against this backdrop, it is of significant importance that the medical profession is educated with the relevant legal standards that are governing their daily practice. Educating the medical profession should start from the undergraduate level at the University with a holistic medical curriculum that combines lectures and workshop discussion of case studies that relates to the needs of the society and the demands of law together with medical ethics. The learning experiences should provide opportunities for medical students to develop and sustain the ideals of medical professionalism in the contemporary healthcare setting. Through a holistic legal education, the medical profession will ultimately be equipped to face the contemporary challenges, safeguard patient safety goals, and eventually provide a more harmonious interface between medicine and law. By employing qualitative methods of research, this research paper will highlight the importance of educating the medical profession with developing legal standards and propose recommendations for the ideals that are required for a holistic medical curriculum and education process that will ultimately prepare the medical profession in facing the fundamental challenges generated by contemporary legal developments.